UAV survey images of the eastern Endalen slope, Svalbard - Mannerfelt, Erik S. (Zenodo, 2023)
A UAV survey of the eastern hillslope in Endalen, Svalbard . The survey consists of 428 post-processed drone images in a tif format, taken by a DJI Mavic 2 Pro on 8 August 2022. The post-processing consisted of applying regular photographic contrast enhancement and noise reduction procedures in darktable version 4.4.0. The exact filters used are available in the EXIF metadata. This is a supplementary dataset for Hamm et al., in prep. A link to the paper will be available upon publication.